Polysaccharides derived from golden mushroom (Cantharellus cibarius Fr.) modulate gut microbiota and enhance intestinal barrier function to ameliorate dextran sulfate sodium-induced colitis in mice - Alioui, Yamina; Ullah, Hidayat; Ali, Sharafat; Rahman, Mujeeb Ur; Elkharti, Maroua; Farooqui, Nabeel Ahmed; Rehman, Ata Ur; Ilyas, Muhammad; Alsholi, Duaa M.; Siddiqi, Nimra Zafar; Ali, Muhsin; Wang, Liang; et al. (Frontiers in Pharmacology, 2024)
IntroductionInflammatory bowel disease (IBD), including ulcerative colitis, is marked by intestinal barrier disruptions, immune system dysregulation, and an imbalance in the gut microbiota. The golden chanterelle mushroom, Cantharellus cibarius Fr., a popular edible mushroom, has shown potential therapeutic benefits. This study examines the therapeutic potential of a crude polysaccharide extract obtained from C. cibarius Fr. (CCP) on intestinal barrier integrity, inflammatory cytokine levels, and gut microbiota composition in a murine model of colitis induced by dextran sulfate sodium (DSS).MethodsTo induce colitis BALB/c mice were provided to consume autoclaved water with 3% DSS for 7 days, followed by 14 days of CCP supplementation. To assess the effects of CCP, histological analysis of colon tissue was performed, gene expression, inflammatory responses, tight junction proteins expression, gut barrier integrity, and cytokines levels were measured and analyzed and 16S rRNA sequencing were evaluated.Results and DiscussionCCP treatment alleviates colitis symptoms by improving body weight, and enhancing intestinal integrity through increased mucin-2 and tight junction protein expression. Additionally, CCP administration regulates the altered immune response by mitigating the expression of pro-inflammatory cytokines and upregulating anti-inflammatory cytokines. Furthermore, CCP supplementation effectively modulates DSS-induced dysbiosis as demonstrated by 16S rRNA sequencing results. These findings suggest that crude polysaccharides from the golden chanterelle mushroom, C. cibarius Fr., hold promise for treating colitis, via strengthening the intestinal barrier, regulating inflammatory responses, and reshaping the gut dysbiosis in a DSS-induced colitis model. CCP offers a novel approach for managing colitis, as a chronic inflammatory condition.